Risk of Symptomatic Infection During a Second Coronavirus Disease 2019 Wave in Severe Acute Respiratory Syndrome Coronavirus 2–Seropositive Individuals. (16th June 2021) - Manica, Mattia; Pancheri, Serena; Poletti, Piero; Giovanazzi, Giulia; Guzzetta, Giorgio; Trentini, Filippo; Marziano, Valentina; Ajelli, Marco; Grazia Zuccali, Maria; Benetollo, Pier Paolo; Merler, Stefano; Ferro, Antonio
Abstract: We analyzed 221 coronavirus disease 2019 cases identified between June 2020 and January 2021 in 6074 individuals screened for immunoglobulin G antibodies in May 2020, representing 77% of residents of 5 Italian municipalities. The relative risk of developing symptomatic infection in seropositive participants was 0.055 (95% confidence interval, .014–.220).